Discovery of a radio transient in M81 - Anderson, Gemma; Miller-Jones, James; Middleton, M.J.; Soria, Roberto; Swartz, D.A.; Urquhart, Ryan; Hurley-Walker, Natasha; Hancock, Paul; Fender, R.P.; Gandhi, P.; Markoff, S.; Roberts, T.P. (OXFORD UNIV PRESS, 2019)
We report the discovery of a radio transient in the spiral galaxy M81. The transient was detected in early 2015 as part of a two-year survey of M81 made up of 12 epochs using the Karl G. Jansky Very Large Array. While undetected on 2014 September 12, the source was first detected on 2015 January 2, from which point it remained visible at an approximately constant luminosity of LR, ν = 1.5 ± 0.1 × 1024 erg s−1 Hz−1 at the observing frequency of 6 GHz for at least 2 months. Assuming this is a synchrotron event with a rise-time between 2.6 and 112 d, the peak luminosity (at equipartition) corresponds to a minimum energy of 1044 ≾ Emin ≾ 1046 erg and jet power of Pmin ∼ 1039 erg s−1, which are higher than most known X-ray binaries. Given its longevity, lack of short-term radio variability, and the absence of any multiwavelength counterpart (X-ray luminosity Lx ≾ 1036 erg s−1), it does not behave like known Galactic or extragalactic X-ray binaries. The M81 transient radio properties more closely resemble the unidentified radio transient 43.78+59.3 discovered in M82, which has been suggested to be a radio nebula associated with an accreting source similar to SS 433. One possibility is that both the new M81 transient and the M82 transient may be the birth of a short-lived radio bubble associated with a discrete accretion event similar to those observed from the ULX Holmberg II X-1. However, it is not possible to rule out other identifications including long-term supernova shockwave interactions with the surrounding medium from a faint supernova or a background active galaxy.